Information management in smart grids: The need for decentralized governance approaches - Marius Buchmann (Jacobs University Bremen, Bremen Energy Research (BER), 2016)
Information management secures the efficient exchange of data (e.g. from smart metering) in smart grids. Currently, national as well as regional information management systems are being developed. We discuss how the size of an information management system, i.e. the region covered by and the number of users connected to it, has an influence on the level of innovation in the process of the data exchange. Based on insights from the theory of fiscal federalism we argue that neither of the extremes of national (central) and decentralized governance approaches for information management will be optimal. We discuss how the market can determine the optimal degree of decentralization. If information management shall enable smart grids, then we show that the network operator needs to be able to incentivize network users to join and participate in an information management system to internalize externalities. Then, the size of the governance of information management systems will be linked to the network areas on the distribution grid level.
Keywords: 330; Smart Grid; Information Management; data exchange; fiscal federalism; size